Origin of scuffing in grey cast iron-steel tribo-system. (15th February 2017) - Saeidi, F.; Taylor, A.A.; Meylan, B.; Hoffmann, P.; Wasmer, K.
Abstract: The failure mechanism known as scuffing is a major problem in lubricated sliding mechanical components, specifically for those tribological systems working under starved lubrication conditions. It occurs suddenly and often results in loss of component functionality, and thus high repair costs. Despite the extensive studies on scuffing over the past 80 years, the basic mechanism of scuffing is not yet well understood. In the present study, a cast iron-steel tribo-system working under starved lubrication conditions, which resembles a semi journal bearing used in a cutting machine, with the dominant scuffing failure mechanism is investigated. Based on the experimental observations in this work, a new theory is proposed for initiation of scuffing in this cast iron-steel tribo-system. According to the proposed theory, scuffing initiates when the tribo-film iron oxide reduces to α-iron providing metal-metal contact and, consequently, strong adhesion between the sliding surfaces. The reduction of the oxide takes place due to a temperature increase at the contacting asperities together with the presence of carbon, coming from either the lubricant or graphite flakes of cast iron, as the reducing agent. Graphical abstract: Highlights: The scuffing mechanism in grey cast iron-steel tribo-system working under starved lubrication conditions is investigated. The scuffed regions of tribo-pairs are deeply characterized by SEM, TEM, and EELS. A new theory for scuffing initiation is proposed. Scuffing initiates when the tribo-film iron oxide reduces to iron and metal-metal contact and, thus adhesion take place.